Gender disparity in speakers of the European Orthodontic Society conferences held between 2015 and 2020: a cross-sectional report. (27th May 2022) - Koletsi, Despina; Papadopoulou, Alexandra K
Summary: Objectives: To assess the representation of female scientists as speakers of blindly selected oral presentations or invited speakers in the latest European Orthodontic Society (EOS) conferences between 2015 and 2020. To examine the association with a number of study- and author-related characteristics. Materials and methods: Abstract books and programmes of the EOS conferences held between 2015 and 2020, were electronically searched to identify the gender of all speakers. The following predictor variables were assessed: year, continent of authorship, number of centres, number of authors involved, study design, study topic, and presentation as a WJB Houston Award nominee. Results: A total of 312 oral presentations were recorded with almost even distribution of female/male gender. In the majority of oral presentations, a European-origin speaker affiliation was confirmed (208/312; 66.7%), with a relatively equal representation of women ( P = 0.05). Seniority in authorship of oral presentations belonged to male scientists (209/312; 67%). Furthermore, a total of 84 invited speakers were identified, of which only 15 (17.9%) were female, indicating a substantial gender gap. No more than four women were invited to lecture annually, compared to a minimum of 10 male scientists. Overall, a significant difference was recorded for the odds of a female scientist to be invited as a speaker in the EOS conference (range of odds across years: 0.20–0.36), compared to the odds for conducting an oral presentation in the same context and timescale (range of odds across years: 0.75–1.45) (Mantel–Haenszel test for homogeneity, P -value < 0.001). Limitations: Findings were based solely on the annual orthodontic conference of the EOS, without further insights on national conferences, or identification of wide-range timescale effects. Conclusions and implications: Gender disparity related to invited speakers at the EOS 2015–20 annual conferences was unequivocally confirmed. Nevertheless, gender differences were not identified in oral presentations. Firm efforts to ensure female scientist's voice is equally represented are needed including a move from theory to practice.